Sosialisasi Website PPDB Pada Yayasan Busyri Al Ali Untuk Peningkatan Layanan Siswa [Socialization of the PPDB Website at Busyri Al Ali Foundation for Improving Student Services] - Tri Deviasari Wulan; Fajar Annas Susanto; Tri Wahyuni Bintarti; Heni Agustina (UKInstitute, 2026)
The purpose of this community service activity is to conduct outreach and mentoring on the use of the New Student Admissions website (PPDB website) at the Busyri Al Ali Foundation. This website was built to help smooth the process of admitting new students and make it easier for prospective parents to complete the registration process. In the current student admissions system, the committee must enter the data of registered students along with the identities of their parents one by one in the school ledger. Another problem is that prospective parents have difficulty in obtaining new student registration information, causing the number of new students to tend to decrease every year. Website outreach was conducted to introduce the PPDB website to the entire academic community within the Busyri Al Ali Foundation. This can make it easier for the entire academic community to introduce the school and help prospective parents to register independently. The results of the outreach showed an increase in participant understanding from the results of the outreach activities. This is indicated by an increase in posttest results of 100% from the pretest results conducted before the outreach activities of 78%. In addition, mentoring activities were also carried out to ensure the PPDB Team can operate the system optimally. Mentoring was carried out for one month in a hybrid manner to ensure the admin can operate the system. During the mentoring activities, several evaluations were carried out regarding obstacles in using the system at the school and the difficulties faced by prospective parents in making online payments. Abstrak. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk melakukan sosialisasi dan pendampingan penggunaan website Penerimaan Peserta Didik Baru (PPDB) di lingkungan Yayasan Busyri Al Ali. Website ini dibangun untuk membantu kelancaran proses penerimaan siswa baru dan mempermudah calon orang tua siswa dalam melakukan proses pendaftaran. Sistem penerimaan siswa saat ini masih menggunakan metode konvensional sehingga panitia PPDB harus memasukkan data siswa yang mendaftar beserta identitas orang tua wali satu-persatu pada buku besar sekolah. Selain itu, kesulitan dalam mendapatkan informasi PPDB pada sekolah di lingkungan Yayasan Busyri Al Ali juga menyebabkan jumlah siswa baru cenderung menurun setiap tahun. Sosialisasi website dilakukan untuk memperkenalkan website PPDB kepada seluruh civitas akademik di lingkungan Yayasan Busyri Al Ali. Hal ini dapat mempermudah seluruh sivitas akademik dalam memperkenalkan sekolah dan membantu para calon orang tua murid untuk melakukan pendaftaran secara mandiri. Hasil sosialisasi menunjukkan adanya peningkatan pemahaman peserta dari hasil kegiatan sosialisasi. Hal ini ditunjukkan dengan peningkatan hasil posttest sebesar 100% dari hasil prestest yang dilakukan sebelum kegiatan sosialisasi sebesar 78%. Selain itu, Kegiatan pendampingan juga dilakukan untuk memastikan Tim PPDB dapat mengoperasikan sistem secara optimal . Pendampingan dilaksanakan selama satu bulan secara hybrid untuk memastikan admin dapat mengoperasikan sistem. Selama kegiatan pendampingan dilaksanakan terdapat beberapa evaluasi terkait kendala penggunaan sistem di sekolah dan kesulitan yang dihadapi oleh calon orang tua siswa dalam melakukan pembayaran secara online.